Disruptive technology for integrating bioremediation and biodiesel production from persistent toxic aromatic wastes using termite gut yeasts - Sameh S. Ali; Rania Al-Tohamy; Jianzhong Sun (Environmental Chemistry and Ecotoxicology)
Termite gut yeasts represent a highly promising yet underexplored resource for the integrated bioremediation of aromatic wastes and biodiesel production. These yeasts possess a remarkable ability to degrade complex aromatic compounds, such as lignin-derived phenolics and azo dye intermediates, while simultaneously accumulating lipids, which can be used for biofuel production. However, several challenges, including low lipid yield, toxicity from aromatic intermediates, scalability issues, and high nutrient requirements, limit their industrial application. To overcome these limitations, advanced metabolic engineering, enzyme optimization, and bioreactor design are essential. This review explores the unique advantages of termite gut yeasts, their current deficiencies, and the potential of novel biotechnological approaches such as synthetic biology, systems biology, and co-culture systems. The paper also discusses a strategic roadmap for optimizing termite yeasts for large-scale industrial applications, including the development of clustered regularly interspaced short palindromic repeats (CRISPR) tools, multi-zone bioreactors, and collaborative partnerships with industries. The integration of bioremediation and biodiesel production presents a disruptive and sustainable technology that, if optimized, could revolutionize both waste management and renewable energy sectors.